Framing Culture in EFL Textbooks: A Critical Discourse Analysis at Islamic School - Fajrin Diana Putri; Djatmika Djatmika; Kristian Adi Putra (STAI Hubbulwathan Duri, 2023)
This present study aims to explore the cultural values represented in the local EFL textbook as a source of learning materials in Islamic Junior High Schools. This study implemented a qualitative approach as a research design. Three English teachers as participants were recruited purposively. The data collected from textbook analysis using the types of speech acts, and politeness strategies through the theory of Critical Discourse Analysis. Semi-structured interviews were conducted to strengthen the data. Then, the data were analyzed thematically. The study revealed that local English textbooks effectively represented cultural values and beliefs. The finding showed that the EFL local textbooks effectually encourage cultural awareness and English language proficiency among students. The cultural values performed in the textbook are greetings, politeness, self-introduction, hobbies, and family interactions, which exhibit the polite culture of how Indonesians communicate. The representation of family lunch highlighted the tradition that shapes Indonesian culture. Additionally, it implied that the teachers perceived the content in the textbook because it highlights moral values that are suitable in Indonesian culture. It has a significant implication for establishing English curricula to construct a proper local English textbook for Islamic junior high school students. This study demonstrated that local English textbooks included interesting and collaborative activities that highlighted Islamic traditions, fostering tolerance and respect. It also highlighted moral and cultural values that students could use to develop good manners.